2022
DOI: 10.3389/fnagi.2022.834331
|View full text |Cite
|
Sign up to set email alerts
|

GWLS: A Novel Model for Predicting Cognitive Function Scores in Patients With End-Stage Renal Disease

Abstract: The scores of the cognitive function of patients with end-stage renal disease (ESRD) are highly subjective, which tend to affect the results of clinical diagnosis. To overcome this issue, we proposed a novel model to explore the relationship between functional magnetic resonance imaging (fMRI) data and clinical scores, thereby predicting cognitive function scores of patients with ESRD. The model incorporated three parts, namely, graph theoretic algorithm (GTA), whale optimization algorithm (WOA), and least squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Firstly, the aLp, aLambda, Eglobal, and corresponding cognitive function scores of 40 subjects in the ESRD group were taken as the dataset D. Then, the whole data set was randomly divided into 40 pieces, 39 of which were used as training set S and 1 as test set T in turn for verification. This article selects mean absolute error (MAE) and mean absolute percentage error (MAPE) as evaluation standard 30 MAE is defined as: MAE=1nfalse∑i=1ntrueŝisi …”
Section: Experiments and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, the aLp, aLambda, Eglobal, and corresponding cognitive function scores of 40 subjects in the ESRD group were taken as the dataset D. Then, the whole data set was randomly divided into 40 pieces, 39 of which were used as training set S and 1 as test set T in turn for verification. This article selects mean absolute error (MAE) and mean absolute percentage error (MAPE) as evaluation standard 30 MAE is defined as: MAE=1nfalse∑i=1ntrueŝisi …”
Section: Experiments and Resultsmentioning
confidence: 99%
“…This article selects mean absolute error (MAE) and mean absolute percentage error (MAPE) as evaluation standard. 30 1. MAE is defined as:…”
Section: Experiments Settingsmentioning
confidence: 99%
“…Meanwhile, the AUC of Elocal accounted for the highest proportion in the feature set. Obviously, the AUC of Elocal was selected as the feature to construct GPSV [ 30 ], GPLSV [ 31 ], GPWLSV [ 32 ], and GPLWLSV for predicting the clinical scores of cognitive functions in ESRD patients [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…WOA can optimize the selection strategy of kernel function parameters and further improve the operating efficiency of the model ( Zhang et al, 2018 ). The combination of LSSVRM and WOA takes work efficiency and prediction accuracy into account ( Zhang et al, 2022 ). In our study, the prediction models based on functional networks showed a relatively great prediction accuracy, with the prediction accuracy based on combined global and nodal measures being slightly higher than that based only on a single type of measures.…”
Section: Discussionmentioning
confidence: 99%
“…Further, we tentatively predicted the cognitive function of ESRD patients using topological properties as features based on the individual level. The least squares support vector regression machine (LSSVRM) was used to build a prediction model, and the whale optimization algorithm (WOA) was used to optimize model parameters ( Zhang et al, 2022 ). In conclusion, our study attempted to improve the possibility of early diagnosis and neuroprotective treatments for ESRD patients by using predictive models based on neuroimaging techniques.…”
Section: Introductionmentioning
confidence: 99%